Momentary partner involvement in diabetes self-care and continuously measured glucose: a dynamic analysis - Soriano, Emily C. (2023)
This study examined the dynamic, real-time associations between partner involvement in diabetes self-care and continuous glucose monitor (CGM) metrics in adults with type 2 diabetes.